Promoting students’ critical speaking skill through Plus-Minus-Interesting (PMI) strategies : a case study of Indonesian junior high schools - Sri Setyarini,; Gustine, Gin Gin; Harto, Sri; Muslim, Ahmad Bukhori (Penerbit Universiti Kebangsaan Malaysia, 2021)
Initiated from in-depth observations on the performance of English teachers at junior high school level, this study analysed teachers’ ways of integrating teaching materials and implementing learning strategies that empowered critical thinking frameworks. A case study design was employed to investigate how Plus-Minus-Interesting (PMI) learning strategies in telling daily life stories improved students’ critical speaking skill (CSS) and to identify the constraints faced by the teachers in implementing PMI learning strategies to overcome their teaching problems. Six English teachers from different junior high schools in North Bandung, Indonesia and their students were recruited as subjects of this study. Classroom observation, in-depth interviews and some relevant documents were administered to collect the data. The data were then described, coded, categorised, and analysed to answer the research questions. The results of observations indicate that PMI learning strategies in daily life stories were executed in three stages, including the opening, core, and closing. These stages were performed through several main activities, from brainstorming to playing games, from storytelling to doing a focused-group discussion, and from story mapping to evaluating. In addition, the results of interviews and documents analysis show that this learning model could promote students’ enthusiasm in the learning activities and the students were able to convey ideas by referring to their daily problems exposed in the contents of daily life stories.